2010
DOI: 10.1002/glia.21054
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin polymerization promoting protein (TPPP/p25) as a marker for oligodendroglial changes in multiple sclerosis

Abstract: Multiple sclerosis (MS) is an idiopathic chronic inflammatory demyelinating disease of the central nervous system with variable extent of remyelination. Remyelination originates from oligodendrocyte (OG) precursor cells, which migrate and differentiate into mature OG. Tubulin polymerization promoting protein (TPPP/p25) is located in mature OG and aggregates in oligodendroglial cytoplasmic inclusions in multiple system atrophy. We developed a novel monoclonal anti-TPPP/p25 antibody to quantify OG in different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 41 publications
5
53
1
1
Order By: Relevance
“…the oligodendroglial cytoplasm and all oligodendroglial processes [7,8], two studies previously reported that TPPP is localized in the nucleus [10,20], consistent with the present data. Höftberger and colleagues previously analyzed the localization of TPPP in the human brain by immunohistochemistry and immunoelectron microscopy, and showed that TPPP was localized in oligodendroglial nuclei as well as its cytoplasm [10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…the oligodendroglial cytoplasm and all oligodendroglial processes [7,8], two studies previously reported that TPPP is localized in the nucleus [10,20], consistent with the present data. Höftberger and colleagues previously analyzed the localization of TPPP in the human brain by immunohistochemistry and immunoelectron microscopy, and showed that TPPP was localized in oligodendroglial nuclei as well as its cytoplasm [10].…”
Section: Discussionsupporting
confidence: 93%
“…Höftberger and colleagues previously analyzed the localization of TPPP in the human brain by immunohistochemistry and immunoelectron microscopy, and showed that TPPP was localized in oligodendroglial nuclei as well as its cytoplasm [10]. Acevedo and colleagues also found similar nuclear localization of TPPP in the non-neuronal cell lines NIH-3T3 and HeLa using immunocytochemistry [20].…”
Section: Discussionmentioning
confidence: 97%
“…Though the neuropathological alterations in MS are results of a complex aetiology including autoimmunity, demyelination, neuronal and axonal degeneration, the central role of oligodendrocytes has also been suggested [15], which gives our observations a wider implication. The interrelation between mitochondrial leukoencephalopathies and MS is well exemplified by the fact that the above mentioned cuprizone intoxication, presenting with a highly similar neuropathology to that observed in KSS and FL-PGC-1α-deficient mice in our study, is in fact a widely applied toxin model of MS [1,27].…”
Section: Discussionmentioning
confidence: 67%
“…distinct CNS diseases such as glioma (brain tumor) [13], multiple sclerosis (demyelination) [14,15] or synucleinopathies (pathological inclusions) [16]. In fact, TPPP/p25 is able to induce α-synuclein (SYN) aggregation [17] in vitro; however, its overexpression and co-localization with SYN in human brain is a characteristic symptom of Parkinson's disease [16], thus we have suggested TPPP/p25 as a biomarker of synucleinopathies [16].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 89%